2015
DOI: 10.5301/hipint.5000307
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Gentamicin and Vancomycin Released from an Antibiotic Containing Bone Cement in Patients Undergoing a Septic One-Stage Total Hip Arthroplasty (THA) Revision: A Monocentric Open Clinical Trial

Abstract: Slow absorption of both antibiotics after release from the cement resulted in plasma concentrations well below toxic levels and did not result in a critical systemic concentration potientially inducing bacterial resistance. The treatment with this novel bone cement was assessed as efficacious and was very well tolerated by all patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The mean postoperative maximum gentamicin plasma concentration at 5.85 h was 209.65 ng/mL. For vancomycin, a mean postoperative maximum plasma concentration of 134.64 ng/mL was determined at 20.03 h. The authors concluded that there was slow absorption of both antibiotics after release from the cement, resulting in plasma concentrations well below toxic levels, which would not result in a critical systemic concentration potentially inducing bacterial resistance. In any case, ALBC are safe from the pharmacotherapeutical point of view, with a very low systemic absorption.…”
Section: Release Kineticsmentioning
confidence: 97%
“…The mean postoperative maximum gentamicin plasma concentration at 5.85 h was 209.65 ng/mL. For vancomycin, a mean postoperative maximum plasma concentration of 134.64 ng/mL was determined at 20.03 h. The authors concluded that there was slow absorption of both antibiotics after release from the cement, resulting in plasma concentrations well below toxic levels, which would not result in a critical systemic concentration potentially inducing bacterial resistance. In any case, ALBC are safe from the pharmacotherapeutical point of view, with a very low systemic absorption.…”
Section: Release Kineticsmentioning
confidence: 97%
“…Local delivery of antibiotics like gentamicin or vancomycin has been long applied in bone cements that are used to fix prosthetic implants . However, a number of recent studies support the lack of efficacy of these antibiotic‐loaded bone cements (AL‐BC) .…”
Section: Antimicrobial Coatingsmentioning
confidence: 99%
“…In cemented THAs we have been using the Optipac Refobacin Bone Cement R system (Zimmer-Biomet, Dieticon, Switzerland) with the 40 g package for cup fixation and 60 g mixed for stem fixation. In the 40 g of the cement polymer is 0.5 g of active gentamicin, which has an established bactericidal effect on particularly gram-positive organisms like Staphylococcus aureus and CoNS (Kendoff et al, 2016;Khassebaf et al, 2015). Cutibacterium acnes growing in biofilm has proven susceptibility to locally administered gentamicin (Ramage et al, 2003).…”
Section: Discussionmentioning
confidence: 99%